Boron complexes of π-extended nitroxide ligands exhibiting three-state redox processes and near-infrared-II (NIR-II) absorption properties. Issue 36 (30th August 2022) - Nakamura, Marika; Hyakutake, Risa; Morisako, Shogo; Sasamori, Takahiro; Mizuhata, Yoshiyuki; Tokitoh, Norihiro; Nakashima, Kouichi; Fukumoto, Hiroki; Agou, Tomohiro
Abstract : Boron complexes of redox-active nitroxide ligands exhibited reversible redox processes involving aminoxide, nitroxide radical, and oxoammonium cation ligands. The nitroxide radical complexes exhibited intense absorptions in the NIR-II region. Abstract : Persistent radicals have attracted increasing attention owing to their fascinating properties, including multi-step redox and long-wavelength absorption characteristics. In this study, boron complexes with π-extended nitroxide ligands were synthesised via Buchwald–Hartwig amination reactions of the corresponding boron-nitroxide complex and diarylamines. These nitroxide complexes exhibited two-step and reversible one-electron oxidation processes, suggesting stable redox triads involving anionic aminoxide, neutral nitroxide-radical, and cationic oxoammonium ligands. Cationic boron complexes of the nitroxide radical ligands were obtained via chemical oxidation of the aminoxide complexes and structurally characterised. The cationic nitroxide-radical complexes exhibited strong absorptions at approximately 1100 nm, demonstrating their potential as near-infrared (NIR)-II-active functional dyes.